An Expedition of Pain and Despondency in Philip Roth’s The Ghost Writer. - VERMA, MANVI (International Journal of Psychosocial Rehabilitation, 2020)
Philip Milton Roth, a marvelous American novelist who was splendidly famous for his fathomless examination of American identity. His works are stuffed with autobiographical ascendancy and supremacy as he is one of the foremost outstanding writers of America’s postmodern era. In the itinerary of a really long journey and career, Philip Milton Roth took on several guises-—primarily versions of himself—within the exploration of what it means to be an American novelist and a Jew. He was actually a titleist of Eastern European novels. Roth’s fiction centers around semi-autobiographical motifs, whereas conveying the perils of making connections between an author and his fictional lives and voices self-consciously, such relationships and connections include narrators and protagonists like Nathan Zuckerman and David Keplish. Though Roth’s writings usually explored the soul of expertise in America, the author rejected being labelled a Jewish American author.